Design model of vocational skills training evaluation / Shadni Wardiah Shaharir @ Saharir - Shaharir @ Saharir, Shadni Wardiah (2012)
Current vocational education system in Malaysia is insufficient in providing skilled human resources to fulfil the needs of skills industry. Current vocational skills training evaluation approach has been criticized to be ineffective by the industry itself. This is due to evaluation information is not being used for improvement purpose. Centre of Instructor and Advanced Skills Training (C1AST) as one of the skills institutes in Malaysia is in the planning stage of developing an evaluation system for their training courses. Therefore, an effective design model of vocational skills training evaluation is required to ensure any IT solution that will benefit CIAST and the skills industry in the future. This research is focused to propose a design model used for evaluating the vocational skills training courses CIAST. The objectives of this research are to identify the principles of vocational skills training evaluation, to select the training evaluation criteria for vocational skills training courses and finally to synthesize a design model of vocational skills training evaluation for CIAST. Further elaboration on CIAST, problem background and literature review are included in this research. Delphi Study is used as the research methodology for data collection and the analysis of this research is done by using Analytical Hierarchy Process (AHP). The result shows criteria prioritization by consensus-building retrieved from Delphi Study to be structured into a design model for vocational skills training evaluation.